Open Access

Some identities on Bernoulli and Euler polynomials arising from the orthogonality of Laguerre polynomials

Advances in Difference Equations20122012:201

https://doi.org/10.1186/1687-1847-2012-201

Received: 8 August 2012

Accepted: 6 November 2012

Published: 22 November 2012

Abstract

In this paper, we derive some interesting identities on Bernoulli and Euler polynomials by using the orthogonal property of Laguerre polynomials.

1 Introduction

The generalized Laguerre polynomials are defined by
exp ( x t 1 t ) ( 1 t ) α + 1 = n = 0 L n α ( x ) t n ( α Q  with  α > 1 ) .
(1.1)
From (1.1), we note that
L n α ( x ) = r = 0 n ( 1 ) r ( n + α n r ) x r r ! ( see [1–3] ) .
(1.2)
By (1.2), we see that L n α ( x ) is a polynomial with degree n. It is well known that Rodrigues’ formula for L n α ( x ) is given by
L n α ( x ) = x α e x n ! ( d n d x n ( e x x n + α ) ) ( see [1–3] ) .
(1.3)
From (1.3) and a part of integration, we note that
0 x α e x L m α ( x ) L n α ( x ) d x = Γ ( α + n + 1 ) n ! δ m , n ,
(1.4)
where δ m , n is a Kronecker symbol. As is well known, Bernoulli polynomials are defined by the generating function to be
t e t 1 e x t = e B ( x ) t = n = 0 B n ( x ) t n n ! ( see [1–29] ) ,
(1.5)

with the usual convention about replacing B n ( x ) by B n ( x ) .

In the special case, x = 0 , B n ( 0 ) = B n are called the n th Bernoulli numbers. By (1.5), we get
B n ( x ) = l = 0 n ( n l ) B n l x l ( see [1–29] ) .
(1.6)
The Euler numbers are defined by
E 0 = 1 , ( E + 1 ) n + E n = 2 δ 0 , n ( see [27, 28] ) ,
(1.7)

with the usual convention about replacing E n by E n .

In the viewpoint of (1.6), the Euler polynomials are also defined by
E n ( x ) = ( E + x ) n = l = 0 n ( n l ) E n l x l ( see [11–24] ) .
(1.8)
From (1.7) and (1.8), we note that the generating function of the Euler polynomial is given by
2 e t + 1 e x t = e E ( x ) t = n = 0 E n ( x ) t n n ! ( see [15–29] ) .
(1.9)
By (1.5) and (1.9), we get
2 e t + 1 e x t = 1 t ( 2 2 2 e t + 1 ) ( t e x t e t 1 ) = 2 n = 0 ( l = 0 n E l + 1 l + 1 ( n l ) B n l ( x ) ) t n n ! .
(1.10)
Thus, by (1.10), we see that
E n ( x ) = 2 l = 0 n ( n l ) E l + 1 l + 1 B n l ( x ) .
(1.11)
By (1.7) and (1.8), we easily get
t e t 1 e x t = t 2 ( 2 e x t e t + 1 ) + ( t e t 1 ) ( 2 e x t e t + 1 ) .
(1.12)
Thus, by (1.12), we see that
B n ( x ) = k = 0 , k 1 n ( n k ) B k E n k ( x ) .
(1.13)
Throughout this paper, we assume that α Q with α > 1 . Let P n = { p ( x ) Q [ x ] | deg p ( x ) n } be the inner product space with the inner product
p ( x ) , q ( x ) = 0 x α e x p ( x ) q ( x ) d x ,

where p ( x ) , q ( x ) P n . From (1.4), we note that { L 0 α ( x ) , L 1 α ( x ) , , L n α ( x ) } is an orthogonal basis for P n .

In this paper, we give some interesting identities on Bernoulli and Euler polynomials which can be derived by an orthogonal basis { L 0 α ( x ) , L 1 α ( x ) , , L n α ( x ) } for P n .

2 Some identities on Bernoulli and Euler polynomials

Let p ( x ) P n . Then p ( x ) can be generated by { L 0 α ( x ) , L 1 α ( x ) , , L n α ( x ) } in P n to be
p ( x ) = k = 0 n C k L k α ( x ) ,
(2.1)
where
p ( x ) , L k α ( x ) = C k L k α ( x ) , L k α ( x ) = C k 0 x α e x L k α ( x ) L k α ( x ) d x = C k Γ ( α + k + 1 ) k ! .
(2.2)
From (2.2), we note that
C k = k ! Γ ( α + k + 1 ) p ( x ) , L k α ( x ) = k ! Γ ( α + k + 1 ) 1 k ! 0 ( d k d x k x k + α e x ) p ( x ) d x = 1 Γ ( α + k + 1 ) 0 ( d k d x k x k + α e x ) p ( x ) d x .
(2.3)
Let us take p ( x ) = m = 0 , m 1 n ( n m ) B m E n m ( x ) P n . Then, from (2.3), we have
C k = 1 Γ ( α + k + 1 ) 0 ( d k d x k x k + α e x ) m = 0 , m 1 n ( n m ) B n E n m ( x ) d x = ( 1 ) k Γ ( α + k + 1 ) m = 0 , m 1 n k l = k n m ( n m ) ( n m l ) B m E n m l l ! ( l k ) ! 0 x l + α e x d x = ( 1 ) k Γ ( α + k + 1 ) m = 0 , m 1 n k l = k n m ( n m ) ( n m l ) B m E n m l l ! ( l k ) ! Γ ( l + α + 1 ) = ( 1 ) k m = 0 , m 1 n k l = k n m ( n m ) ( n m l ) B m E n m l l ! ( l k ) ! ( l + α ) ( l + α 1 ) α ( α + k ) ( α + k 1 ) α = ( 1 ) k n ! m = 0 , m 1 n k l = k n m B m m ! E n m l ( n m l ) ! ( l + α l k ) .
(2.4)

Therefore, by (2.1) and (2.4), we obtain the following theorem.

Theorem 2.1 For n Z + , we have

From (1.13), we can derive the following corollary.

Corollary 2.2 For n Z + , we have
B n ( x ) = n ! k = 0 n ( 1 ) k ( m = 0 , m 1 n k l = k n m B m m ! E n m l ( n m l ) ! ( l + α l k ) ) L k α ( x ) .
Let us take p ( x ) = l = 0 n ( n l ) E l + 1 l + 1 B n l ( x ) . By the same method, we get
C k = 1 Γ ( α + k + 1 ) 0 ( d k d x k x k + α e x ) l = 0 n ( n l ) E l + 1 l + 1 B n l ( x ) d x = 1 Γ ( α + k + 1 ) l = 0 n k m = 0 n l ( n l ) ( n l m ) E l + 1 l + 1 B n l m 0 ( d k d x k x k + α e x ) x m d x = ( 1 ) k Γ ( α + k + 1 ) l = 0 n k m = k n l ( n l ) ( n l m ) E l + 1 l + 1 B n l m m ! ( m k ) ! Γ ( m + α + 1 ) = ( 1 ) k l = 0 n k m = k n l ( n l ) ( n l m ) m ! ( m k ) ! E l + 1 ( l + 1 ) B n l m ( α + m ) ( α + m 1 ) α ( α + k ) ( α + k 1 ) α = ( 1 ) k n ! l = 0 n k m = k n l ( α + m m k ) E l + 1 ( l + 1 ) ! B n l m ( n l m ) ! .
(2.5)

Therefore, by (1.11), (2.1), and (2.5), we obtain the following theorem.

Theorem 2.3 For n Z + , we have
E n ( x ) 2 = n ! k = 0 n ( 1 ) k ( l = 0 n k m = k n l ( α + m m k ) E m + 1 ( m + 1 ) ! B n m l ( n m l ) ! ) L k α ( x ) .
For n N with n 2 and m Z + with n m 0 , we have
B n m ( x ) B m ( x ) = r { ( n m 2 r ) m + ( m 2 r ) ( n m ) } B 2 r B n 2 r ( x ) n 2 r + ( 1 ) m + 1 ( n m ) ! m ! n ! B n P n ( see [8] ) .
(2.6)
Let us take p ( x ) = B n m ( x ) B m ( x ) P n . Then p ( x ) can be generated by an orthogonal basis { L 0 α ( x ) , L 1 α ( x ) , , L n α ( x ) } in P n to be
p ( x ) = k = 0 n C k L k α ( x ) .
(2.7)
From (2.3), (2.6), and (2.7), we note that
C k = 1 Γ ( α + k + 1 ) 0 ( d k d x k x k + α e x ) p ( x ) d x = 1 Γ ( α + k + 1 ) r = 0 [ n 2 ] { ( n m 2 r ) m + ( m 2 r ) ( n m ) } × B 2 r n 2 r 0 ( d k d x k x k + α e x ) B n 2 r ( x ) d x = 1 Γ ( α + k + 1 ) r = 0 [ n 2 ] { ( n m 2 r ) m + ( m 2 r ) ( n m ) } B 2 r n 2 r × l = 0 n 2 r ( n 2 r l ) B n 2 r l 0 ( d k d x k x k + α e x ) x l d x = 1 Γ ( α + k + 1 ) r = 0 [ n 2 ] l = 0 n 2 r { ( n m 2 r ) m + ( m 2 r ) ( n m ) } ( n 2 r l ) × B 2 r B n 2 r l n 2 r 0 ( d k d x k x k + α e x ) x l d x = ( 1 ) k Γ ( α + k + 1 ) r = 0 [ n k 2 ] l = k n 2 r { ( n m 2 r ) m + ( m 2 r ) ( n m ) } ( n 2 r l ) × B 2 r B n 2 r l l ! ( n 2 r ) ( l k ) ! Γ ( α + l + 1 ) .
(2.8)
It is easy to show that
Γ ( α + l + 1 ) Γ ( α + k + 1 ) ( l k ) ! = ( α + l ) ( α + l 1 ) α Γ ( α ) ( α + k ) ( α + k 1 ) α Γ ( α ) ( l k ) ! = ( α + l ) ( α + l 1 ) ( α + k + 1 ) ( α k ) ! = ( α + l l k ) .
(2.9)
By (2.8) and (2.9), we get
C k = ( 1 ) k r = 0 [ n k 2 ] l = k n 2 r { ( n m 2 r ) m + ( m 2 r ) ( n m ) } × ( n 2 r l ) ( α + l l k ) l ! B 2 r B n 2 r l ( n 2 r ) .
(2.10)

Therefore, by (2.7) and (2.10), we obtain the following theorem.

Theorem 2.4 For n N with n 2 and m Z + with n m 0 , we have
B n m ( x ) B m ( x ) = k = 0 n ( 1 ) k { r = 0 [ n k 2 ] l = k n 2 r ( ( n m 2 r ) m + ( m 2 r ) ( n m ) ) × ( n 2 r l ) ( α + l l k ) l ! B 2 r B n 2 r l ( n 2 r ) } L k α ( x ) .
It is easy to show that
t 2 e t ( x + y ) ( e t 1 ) 2 = ( x + y 1 ) t 2 e t ( x + y 1 ) e t 1 t 2 d d t ( e t ( x + y 1 ) e t 1 ) .
(2.11)
From (2.11), we have
k = 0 n ( n k ) B k ( x ) B n k ( y ) = ( 1 n ) B n ( x + y ) + ( x + y 1 ) n B n 1 ( x + y ) ( see [11] ) .
(2.12)
Let x = y . Then by (2.12), we get
k = 0 n ( n k ) B k ( x ) B n k ( x ) = ( 1 n ) B n ( 2 x ) + ( 2 x 1 ) B n 1 ( 2 x ) .
(2.13)
Let us take p ( x ) = k = 0 n ( n k ) B k ( x ) B n k ( x ) P n . Then p ( x ) can be generated by an orthogonal basis { L 0 α ( x ) , L 1 α ( x ) , , L n α ( x ) } in P n to be
p ( x ) = k = 0 n ( n k ) B k ( x ) B n k ( x ) = k = 0 n C k L k α ( x ) .
(2.14)
From (2.3), (2.13), and (2.14), we can determine the coefficients C k ’s to be
C k = 1 Γ ( α + k + 1 ) 0 ( d k d x k x k + α e x ) p ( x ) d x = 1 Γ ( α + k + 1 ) { ( 1 n ) 0 ( d k d x k x k + α e x ) B n ( 2 x ) d x + n 0 ( d k d x k x k + α e x ) ( 2 x 1 ) B n 1 ( 2 x ) d x } .
(2.15)
By simple calculation, we get
(2.16)
and
(2.17)

Therefore, by (2.13), (2.14), (2.15), (2.16), and (2.17), we obtain the following theorem.

Theorem 2.5 For n Z + , we get

Declarations

Acknowledgements

The authors would like to express their deep gratitude to the referees for their valuable suggestions and comments.

Authors’ Affiliations

(1)
Department of Mathematics, Kwangwoon University
(2)
Department of Mathematics Education, Kyungpook National University
(3)
Hanrimwon, Kwangwoon University
(4)
Division of General Education, Kwangwoon University

References

  1. Carlitz L: An integral for the product of two Laguerre polynomials. Boll. Unione Mat. Ital. 1962, 17(17):25–28.MATHGoogle Scholar
  2. Carlitz L: On the product of two Laguerre polynomials. J. Lond. Math. Soc. 1961, 36: 399–402. 10.1112/jlms/s1-36.1.399View ArticleMATHGoogle Scholar
  3. Cangul N, Kurt V, Ozden H, Simsek Y: On the higher-order w - q -Genocchi numbers. Adv. Stud. Contemp. Math. 2009, 19(1):39–57.MathSciNetGoogle Scholar
  4. Akemann G, Kieburg M, Phillips MJ: Skew-orthogonal Laguerre polynomials for chiral real asymmetric random matrices. J. Phys. A 2010., 43(37): Article ID 375207Google Scholar
  5. Bayad A, Kim T: Identities for the Bernoulli, the Euler and the Genocchi numbers and polynomials. Adv. Stud. Contemp. Math. 2010, 20(2):247–253.MathSciNetMATHGoogle Scholar
  6. Bayad A: Modular properties of elliptic Bernoulli and Euler functions. Adv. Stud. Contemp. Math. 2010, 20(3):389–401.MathSciNetMATHGoogle Scholar
  7. Carlitz L: Note on the integral of the product of several Bernoulli polynomials. J. Lond. Math. Soc. 1959, 34: 361–363. 10.1112/jlms/s1-34.3.361View ArticleMATHGoogle Scholar
  8. Carlitz L: Some generating functions for Laguerre polynomials. Duke Math. J. 1968, 35: 825–827. 10.1215/S0012-7094-68-03587-4MathSciNetView ArticleMATHGoogle Scholar
  9. Costin RD: Orthogonality of Jacobi and Laguerre polynomials for general parameters via the Hadamard finite part. J. Approx. Theory 2010, 162(1):141–152. 10.1016/j.jat.2009.04.002MathSciNetView ArticleMATHGoogle Scholar
  10. Ding D, Yang J: Some identities related to the Apostol-Euler and Apostol-Bernoulli polynomials. Adv. Stud. Contemp. Math. 2010, 20(1):7–21.MathSciNetMATHGoogle Scholar
  11. Hansen ER: A Table of Series and Products. Prentice Hall, Englewood Cliffs; 1975.MATHGoogle Scholar
  12. Kudo A: A congruence of generalized Bernoulli number for the character of the first kind. Adv. Stud. Contemp. Math. 2000, 2: 1–8.MathSciNetMATHGoogle Scholar
  13. Kim T, Choi J, Kim YH, Ryoo CS: On q -Bernstein and q -Hermite polynomials. Proc. Jangjeon Math. Soc. 2011, 14(2):215–221.MathSciNetMATHGoogle Scholar
  14. Kim T: A note on q -Bernstein polynomials. Russ. J. Math. Phys. 2011, 18(1):73–82. 10.1134/S1061920811010080MathSciNetView ArticleMATHGoogle Scholar
  15. Kim T: Some identities on the q -Euler polynomials of higher order and q -Stirling numbers by the fermionic p -adic integral on Z p . Russ. J. Math. Phys. 2009, 16(4):484–491. 10.1134/S1061920809040037MathSciNetView ArticleMATHGoogle Scholar
  16. Kim T: Symmetry of power sum polynomials and multivariate fermionic p -adic invariant integral on Z p . Russ. J. Math. Phys. 2009, 16(1):93–96. 10.1134/S1061920809010063MathSciNetView ArticleMATHGoogle Scholar
  17. Ozden H, Cangul IN, Simsek Y: Multivariate interpolation functions of higher-order q -Euler numbers and their applications. Abstr. Appl. Anal. 2008., 2008: Article ID 390857Google Scholar
  18. Choi J, Kim DS, Kim T, Kim YH: Some arithmetic identities on Bernoulli and Euler numbers arising from the p -adic integrals on Z p . Adv. Stud. Contemp. Math. 2012, 22(2):239–247.MathSciNetMATHGoogle Scholar
  19. Ozden H, Cangul IN, Simsek Y: Remarks on q -Bernoulli numbers associated with Daehee numbers. Adv. Stud. Contemp. Math. 2009, 18(1):41–48.MathSciNetGoogle Scholar
  20. Rim SH, Lee SJ: Some identities on the twisted ( h , q ) -Genocchi numbers and polynomials associated with q -Bernstein polynomials. Int. J. Math. Math. Sci. 2011., 2011: Article ID 482840Google Scholar
  21. Rim SH, Bayad A, Moon EJ, Jin JH, Lee SJ: A new construction on the q -Bernoulli polynomials. Adv. Differ. Equ. 2011., 2011: Article ID 34Google Scholar
  22. Rim SH, Jin JH, Moon EJ, Lee SJ: Some identities on the q -Genocchi polynomials of higher-order and q -Stirling numbers by the fermionic p -adic integral on Z p . Int. J. Math. Math. Sci. 2010., 2010: Article ID 860280Google Scholar
  23. Ryoo CS: On the generalized Barnes type multiple q -Euler polynomials twisted by ramified roots of unity. Proc. Jangjeon Math. Soc. 2010, 13(2):255–263.MathSciNetMATHGoogle Scholar
  24. Ryoo CS: A note on the Frobenius-Euler polynomials. Proc. Jangjeon Math. Soc. 2011, 14(4):495–501.MathSciNetMATHGoogle Scholar
  25. Ryoo CS: Some relations between twisted q -Euler numbers and Bernstein polynomials. Adv. Stud. Contemp. Math. 2011, 21(2):217–223.MathSciNetMATHGoogle Scholar
  26. Ryoo CS: Some identities of the twisted q -Euler numbers and polynomials associated with q -Bernstein polynomials. Proc. Jangjeon Math. Soc. 2011, 14(2):239–248.MathSciNetMATHGoogle Scholar
  27. Simsek Y: Generating functions of the twisted Bernoulli numbers and polynomials associated with their interpolation functions. Adv. Stud. Contemp. Math. (Kyungshang) 2008, 16(2):251–278.MathSciNetMATHGoogle Scholar
  28. Simsek Y: Special functions related to Dedekind-type DC-sums and their applications. Russ. J. Math. Phys. 2010, 17(4):495–508. 10.1134/S1061920810040114MathSciNetView ArticleMATHGoogle Scholar
  29. Simsek Y: On p -adic twisted q - L -functions related to generalized twisted Bernoulli numbers. Russ. J. Math. Phys. 2006, 13(3):340–348. 10.1134/S1061920806030095MathSciNetView ArticleMATHGoogle Scholar

Copyright

© Kim et al.; licensee Springer 2012

This article is published under license to BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.